A preparation method of high thermal conductivity material and its application in LED car lights
By using a composite thermal filler of metal powder loaded with gallium oxide nanosheets and a gallium-based liquid metal in LED headlights, combined with the microcapsule technology of banana pseudostem extract, the problem of poor heat dissipation of LED headlights is solved, and efficient thermal conductivity and stability are achieved.
Patent Information
- Application Number
- CN202411159097.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The heat dissipation of LED headlights during operation is poor, resulting in an increase in the temperature of the LED component, affecting the luminous efficiency and life. Existing thermally conductive materials such as nanometal powders are prone to oxidation and have degraded thermal conductivity; liquid metals are prone to leakage and have high corrosion.
By synthesizing gallium oxide nanosheets, they are loaded on metal powder and mixed with gallium-based liquid metal and coated in a sheet interwoven network structure formed by cellulose nanofibers and hydroxyboron nitride to form a composite thermally conductive filler. At the same time, banana pseudostem extract is mixed with octane to form microcapsules to prevent the extract from leaking and volatilization.
It improves the thermal conductivity of LED headlights, avoids the oxidation of nano-metal powder and leakage of liquid metals, extends the service life and improves performance stability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive materials for LED vehicle lamps, and in particular to a method for preparing a high thermal conductive material and application thereof in LED vehicle lamps. Background Art
[0002] The LED lamp is an electroluminescent semiconductor material chip, which is cured to the bracket with silver glue or white glue, and then the chip and the circuit board are connected with silver wire or gold wire. It is sealed with epoxy resin on all sides to protect the internal core wire. Finally, the shell is installed. As the fourth generation light source, it is used for exterior and interior lighting of automobiles. It has the advantages of energy saving, environmental protection, safety, low energy consumption, and high brightness. It uses high thermal conductivity, high insulation, and high transmittance materials to quickly transfer heat, which can effectively increase the service life of LED lamps. The heat dissipation materials commonly used in packaging are mainly metal aluminum, ceramic materials, and liquid metal materials, and the thermal conductive materials are sprayed onto the LED lamp by spraying.
[0003] When LED lights are working, heat cannot be effectively dissipated, causing the temperature of LED components to rise, which in turn affects their luminous efficiency and lifespan; spraying thermal conductive material nano-metal powder on the surface of LED car lights can effectively improve the thermal conductivity of LED lights, but nano-metal powder is easily combined with oxygen to form an oxide film on the surface of the nano-metal powder, resulting in a decrease in thermal conductivity; using liquid metal as the thermal conductive material of LER lamps can reduce the thermal resistance of LER lamps and improve the heat dissipation performance of LER lamps, but liquid metal is easy to leak and is also corrosive, affecting the use of LED lamps. Summary of the invention
[0004] The invention aims to provide a preparation method of a high thermal conductivity material and its application in an LED car lamp: synthesizing gallium oxide nanosheets from nano metal powder, the synthesized gallium oxide nanosheets have excellent antioxidant properties, and the nano metal powder is prevented from being easily combined with oxygen, and an oxide film is formed on the surface of the nano metal powder, resulting in a decrease in thermal conductivity; the metal powder loaded with the gallium oxide nanosheets is mixed with a gallium-based liquid metal, and the sheet structure contained on the surface of the metal powder can adsorb the gallium-based liquid metal into the sheet gap, so that the metal powder and the gallium-based liquid metal are tightly combined; the composite is coated in a sheet-interwoven network structure formed by cellulose nanofibers and hydroxyboron nitride, providing a thermal conduction path for the gallium-based liquid metal, so that the composite thermal conductive filler has good thermal conductivity; banana pseudostem extract is mixed with octadecane as a core material, and silicon dioxide is used as a wall material to form a microcapsule, which can effectively prevent the leakage and volatilization of the banana pseudostem extract and improve the service life and performance stability of the banana pseudostem extract.
[0005] The technical problems to be solved by the present invention are as follows: when LED car lights are working, heat cannot be effectively dissipated, resulting in an increase in the temperature of LED components, which in turn affects their luminous efficiency and life; spraying nano-metal powder, a thermally conductive material, on the surface of LED car lights can effectively improve the thermal conductivity of LED car lights, but nano-metal powder is easily combined with oxygen to form an oxide film on the surface of the nano-metal powder, resulting in a decrease in thermal conductivity; using liquid metal as the thermal conductive material of LER lamps can reduce the thermal resistance of LER lamps and improve the heat dissipation performance of LER lamps, but liquid metal is easy to leak and is also corrosive, affecting the use of LED lamps.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high thermal conductivity material comprises the following steps:
[0008] S1. The metal powder loaded with gallium oxide nanosheets is mixed with gallium-based liquid metal, and then stirred and reacted with cellulose nanofibers and hydroxyboron nitride to obtain a composite thermal conductive filler.
[0009] Furthermore, the gallium-based liquid metal is selected from gallium-indium-tin liquid metal, and the density is 6.4-6.5 g / cm 3 , the surface tension is 718-720m / Nm.
[0010] Furthermore, the cellulose nanofibers have a length of 0.5-1 μm and a diameter of 10-30 nm.
[0011] Furthermore, the particle size of hydroxyboron nitride is 2-5 μm.
[0012] Furthermore, the composite thermally conductive filler is prepared by the following steps:
[0013] The metal powder loaded with gallium oxide nanosheets and the gallium-based liquid metal are mixed, placed in an oxygen-free environment, and stirred at 20°C for 30 minutes to obtain a composite. Hydroxyboron nitride and cellulose nanofibers are added to deionized water, stirred and reacted at 50°C for 1 hour to form a gel. The composite is added to the gel, and the stirring reaction is continued for 30 minutes. The mixture is then placed in a freeze dryer and freeze-dried at -20°C for 1 hour to obtain a composite thermal conductive filler.
[0014] Among them, the gallium oxide nanosheets contained in the metal powder loaded with gallium oxide nanosheets have excellent compatibility with gallium-based liquid metal, and the lamellar structure contained on the surface of the metal powder can adsorb the gallium-based liquid metal into the lamellar gaps, so that the metal powder and the gallium-based liquid metal are tightly combined.
[0015] Furthermore, the oxygen-containing functional groups on the surface of the cellulose nanofibers can combine with the hydroxyl groups of hydroxyboron nitride through chemical bonds to form a network structure of interlaced sheets, and the gallium ions contained in the modified gallium-based liquid metal can combine with the carboxyl groups contained on the surface of the cellulose nanofibers, so that the composite is coated in the network structure of interlaced sheets, providing a thermal conduction path for the composite gallium-based liquid metal, providing an effective heat transfer path, and enhancing the thermal conductivity.
[0016] Furthermore, the mass ratio of the metal powder loaded with gallium oxide nanosheets to the gallium-based liquid metal is (1-1.4) g:(6-7) g.
[0017] Furthermore, the dosage ratio of hydroxyboron nitride, cellulose nanofibers, deionized water, and the composite is (0.3-0.7) g: (0.6-0.8) g: (45-55) mL: (1-2) g.
[0018] Furthermore, the metal powder loaded with gallium oxide nanosheets is prepared by modifying the surface of nano metal powder with lignin, mixing with a gallium oxide precursor, and then subjecting the mixture to a hydrothermal treatment.
[0019] Furthermore, the nano metal powder is selected from any one of nano nickel powder, nano copper powder and nano aluminum powder.
[0020] Furthermore, the particle size of the nano metal powder is 2-5 μm.
[0021] Furthermore, the gallium oxide precursor is selected from gallium chloride or metallic gallium.
[0022] Furthermore, the hydrothermal treatment temperature is 160-200°C, and the hydrothermal treatment time is 2-4h.
[0023] Furthermore, the metal powder loaded with gallium oxide nanosheets is prepared by the following steps:
[0024] A1. Add lignin and nano-metal powder to deionized water, stir evenly, add 5% by mass sodium hydroxide aqueous solution to adjust the pH value to 10, stir at 70°C for 40 minutes, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10 minutes to obtain pretreated nano-metal powder.
[0025] Among them, under alkaline conditions, the hydroxyl groups contained on the surface of the nanometal powder can be chemically bonded with the oxygen-containing functional groups in the lignin, so that the lignin is coated on the surface of the nanometal powder and carries a large number of phenolic hydroxyl structures, which serve as gallium ion adsorption sites and help to synthesize gallium oxide nanosheets on the nanometal powder.
[0026] Furthermore, the dosage ratio of lignin, nano-metal powder, deionized water, and sodium hydroxide aqueous solution is (3-5) g: (0.1-0.3) g: (45-55) mL: (0.1-0.3) mL.
[0027] A2. Add the gallium oxide precursor to 0.4M hydrochloric acid, stir evenly, add urea, potassium oxalate and polyvinyl pyrrolidone, stir for 30 minutes, add the pretreated nano-metal powder, stir for 30 minutes, place in a hydrothermal reactor, and perform hydrothermal treatment at 180°C for 3 hours. Filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70°C for 30 minutes to obtain a metal powder loaded with gallium oxide nanosheets.
[0028] The gallium oxide precursor is dissolved in hydrochloric acid to release gallium ions, and the hydroxide ions released by the hydrolysis of urea can combine with the gallium ions to form gallium hydroxide precipitates. The phenolic hydroxyl groups contained in the pretreated nano-metal powder can also combine with the gallium ions, so that the gallium ions are adsorbed on the surface of the nano-metal powder. The formed gallium hydroxide precipitates are deposited on the surface of the pretreated nano-metal powder. A hydrothermal reaction is carried out at 180° C., so that the gallium hydroxide is thermally decomposed to form gallium oxide crystals. Potassium oxalate monohydrate and polyvinyl pyrrolidone are used as ligands and surfactants to continue the hydrothermal reaction. The gallium oxide crystals crystallize and grow to form gallium oxide nanosheets, thereby realizing the synthesis of gallium oxide nanosheets on the surface of the pretreated nano-metal powder.
[0029] Furthermore, the dosage ratio of gallium oxide precursor, hydrochloric acid, urea, potassium oxalate, and pretreated nano-metal powder is (0.3-0.7) g: (25-35) mL: (0.2-0.4) g: (0.3-0.34) g: (0.1-0.3) g.
[0030] S2. The microcapsules are surface modified with polysiloxane, and then mixed with hydroxy silicone oil and terephthalic acid to obtain modified silicone resin.
[0031] Furthermore, the polysiloxane is selected from any one of polydimethylsiloxane, polymethylhydrogensiloxane, polyphenylmethylsiloxane and dimethyldiphenylpolysiloxane.
[0032] Furthermore, the viscosity of the hydroxy silicone oil is 80-120 mPa·s, and the mass fraction of hydroxyl group is 2.5-3.5%.
[0033] Furthermore, the modified silicone resin is specifically prepared by the following steps:
[0034] B1. Add polysiloxane and microcapsules to deionized water and ethanol, stir evenly, heat to 60°C, stir and react for 30 minutes, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10 minutes to obtain pretreated microcapsules.
[0035] Among them, the silanol groups in the polysiloxane can be combined with the hydroxyl groups on the surface of the core-shell flame-retardant microcapsules through chemical bonds, so that the polysiloxane is coated on the surface of the flame-retardant microcapsules, providing a large number of organosilicon functional groups that can participate in the synthesis of silicone resins.
[0036] Furthermore, the dosage ratio of polysiloxane, microcapsule, deionized water and ethanol is (2-3) g: (1-1.4) g: (8-12) mL: (45-55) mL.
[0037] B2. Mix hydroxy silicone oil, neopentyl glycol and monobutyl tin oxide, introduce nitrogen, stir and react at 190°C for 2h, cool to 160°C, add pretreated microcapsules and terephthalic acid, heat to 240°C, stir and react until clear and transparent, cool to room temperature, discharge and obtain modified silicone resin.
[0038] Among them, monobutyl tin oxide is used as a catalyst to make hydroxy silicone oil react with neopentyl glycol to expand the molecular weight of hydroxy silicone oil. The hydroxyl groups carried by neopentyl glycol and the hydroxyl groups contained in the polysiloxane in the pretreated microcapsules can undergo polymerization reaction with the carboxyl groups of terephthalic acid to form polyester on the hydroxy silicone oil molecular chain. The pretreated microcapsules are grafted on the silicone polyester molecular chain, giving the silicone polyester excellent flame retardant properties and insulation properties.
[0039] Furthermore, the usage ratio of hydroxy silicone oil, neopentyl glycol, monobutyl tin oxide, pretreated microcapsule and terephthalic acid is (4-4.4) g: (4-4.2) g: (0.01-0.03) g: (1.1-1.3) g: (5.5-6.5) g.
[0040] Furthermore, the microcapsules are prepared by mixing banana pseudostem extract and octadecane as core material and silicon dioxide as wall material, and are specifically prepared by the following steps:
[0041] Banana pseudostem extract, octadecane and tetraethyl silicate are added to ethanol and heated at 50°C for 30 minutes to obtain an oil phase. Anhydrous ethanol, deionized water and hexadecyltrimethylammonium bromide are mixed and stirred at 50°C for 30 minutes to form an aqueous phase. The aqueous phase and the oil phase are mixed and placed in a homogenizer and emulsified at 12000 rpm for 20 minutes. Ammonia water is added to initiate hydrolysis and polycondensation of tetraethyl silicate. After stirring for 2 hours, the mixture is washed three times with deionized water and dried in an oven at 60°C for 10 minutes to obtain microcapsules.
[0042] Among them, the banana pseudostem extract contains lipophilic substances such as silicates, which can interact with octadecane to form a stable core material. The silica formed by the hydrolysis and condensation of tetraethyl silicate is used as the wall material to form core-shell microcapsules, which can effectively prevent the leakage and volatilization of the banana pseudostem extract, improve the service life and performance stability of the banana pseudostem extract, and thus give the thermal conductive material excellent flame retardant and insulating properties.
[0043] Furthermore, the dosage ratio of banana pseudostem extract, octadecane, tetraethyl silicate, ethanol, anhydrous ethanol, deionized water, and hexadecyltrimethylammonium bromide is (2-3) g:(1.6-2) g:(13-17) mL:(18-22) mL:(8-12) mL:(13-17) mL:(0.3-0.7) g.
[0044] Further, the banana pseudostem extract is specifically prepared by the following steps:
[0045] The banana tree is cut to remove the outer sheath and the flower stem, leaving the pseudostem, which is further divided into small pieces and crushed into powder in a grinder. The powder is wrapped in a filter cloth with a pore size of 0.1-0.2 μm, and the filter cloth is squeezed with a hammer to collect juice to obtain a banana pseudostem extract.
[0046] S3. Mix the modified silicone resin, composite thermal conductive filler, bismuth oxide, aluminum oxide and aluminum nitride, place in a mixer and stir for 10-20 minutes, cool, place in a grinder and grind into powder to obtain a high thermal conductive material.
[0047] Among them, composite thermal conductive filler, bismuth oxide, aluminum oxide, and aluminum nitride are added to the modified silicone resin matrix to form a thermal conductive channel in the modified silicone resin, which has good thermal conductivity.
[0048] Furthermore, the mass ratio of modified silicone resin, composite thermal conductive filler, bismuth oxide, aluminum oxide and aluminum nitride is (30-40):(10-15):(2-3):(1-2):(1.2-1.5).
[0049] Furthermore, the particle size of bismuth oxide, aluminum oxide and aluminum nitride is 0.1-2 μm.
[0050] Furthermore, the mixer temperature is 150-200°C.
[0051] Furthermore, compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) In the technical solution of the present invention, lignin is coated on the surface of nano-metal powder and carries a large number of phenolic hydroxyl structures, which serve as gallium ion adsorption sites and are helpful for synthesizing gallium oxide nanosheets on the nano-metal powder; gallium oxide nanosheets are synthesized on the surface of pretreated nano-metal powder, and the synthesized gallium oxide nanosheets have excellent antioxidant properties, which prevents the nano-metal powder from combining with oxygen and forming an oxide film on the surface of the nano-metal powder, resulting in a decrease in thermal conductivity. In addition, the gallium oxide nanosheets form a rough surface with a lamellar structure on the surface of the nano-metal powder, which improves the bonding force between the nano-metal powder and the gallium-based liquid metal, and prevents the nano-metal powder from settling in the gallium-based liquid metal and reducing the thermal conductivity.
[0053] (2) In the technical solution of the present invention, the metal powder loaded with gallium oxide nanosheets is mixed with the gallium-based liquid metal. The lamellar structure on the surface of the metal powder can adsorb the gallium-based liquid metal into the lamellar gaps, so that the metal powder and the gallium-based liquid metal are tightly combined, avoiding the sedimentation of the nano metal powder, which leads to a decrease in the thermal conductivity of the gallium-based liquid metal. In addition, a metal powder with higher thermal conductivity is added to the gallium-based liquid metal to optimize the thermal conductivity of the gallium-based liquid metal. In addition, the metal powder loaded with gallium oxide nanosheets is incorporated into the liquid metal, and its small size structure improves the stability of the liquid metal.
[0054] (3) In the technical solution of the present invention, the composite is coated in a network structure of interlaced sheets formed by cellulose nanofibers and hydroxyboron nitride, forming a core-shell structure with good stability and flexibility, thereby preventing the liquid metal from leaking and affecting the use of the LED lamp. The interlaced network structure provides a thermal conductivity path for the gallium-based liquid metal, so that the composite thermal conductive filler can exert good thermal conductivity, thereby avoiding the liquid metal from being blocked during the coating process and lacking an effective heat transfer path, resulting in a decrease in thermal conductivity. In addition, the formed composite thermal conductive filler is cold sprayed onto the surface of the LED lamp, and the cellulose nanofibers contained on the surface of the composite thermal conductive filler can absorb external stress and improve the mechanical properties of the LED lamp.
[0055] (4) In the technical solution of the present invention, the banana pseudostem extract is rich in calcium phosphate, sodium phosphate, silicate and other elements. During the combustion process, it can promote the silicone resin to form a dense carbon layer, which has good flame retardant properties. The banana pseudostem extract is mixed with octadecane as the core material and silicon dioxide as the wall material to form core-shell microcapsules, which can effectively prevent the leakage and volatilization of the banana pseudostem extract, and improve the service life and performance stability of the banana pseudostem extract. In addition, the banana pseudostem extract interacts with octadecane to form a stable core material. Octadecane can absorb the heat generated during the combustion process, reduce the surface temperature, and improve the flame retardant properties.
[0056] (5) In the technical solution of the present invention, polysiloxane is used to modify the surface of flame-retardant microcapsules, which provide a large number of organosilicon functional groups and can participate in the synthesis of organosilicon resin. The microcapsules coated with polysiloxane are mixed with hydroxy silicone oil, which, as an organosilicon monomer, can undergo polymerization reaction with the carboxyl group of terephthalic acid to form a modified organosilicon resin, thereby achieving the grafting of the microcapsules onto the molecular chain of the organosilicon resin, thereby imparting excellent flame retardant properties. The organosilicon resin also has good insulation properties. When sprayed onto LED headlights, it can shield the conductivity of the added metal thermal conductive filler and improve safety performance. DETAILED DESCRIPTION
[0057] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] The raw materials used in the embodiments of the present invention are as follows: lignin (Shandong Longli Biotechnology Co., Ltd.); nano nickel powder (Zhejiang Yamei Nanotechnology Co., Ltd., purity 99%); gallium chloride (Shandong Kepler Biotechnology Co., Ltd., purity 99%); urea, potassium oxalate, polyvinyl pyrrolidone (Sinopharm Chemical Reagent Company); gallium-indium-tin liquid metal (Suzhou Rongqian Rare Metal Products Co., Ltd., gallium 45-60%, indium 25-30%, tin 5-10%); hydroxyboron nitride (Xi'an Qiyue Biotechnology Co., Ltd.); cellulose nanofibers (Shanghai McLean Biochemical Technology Co., Ltd., carboxyl content of 1.2-3mmol / L); Octadecane (Shanghai McLean Biochemical Technology Co., Ltd., purity 99%); tetraethyl silicate (Aladdin Reagent Co., Ltd., purity 99.9%); polydimethylsiloxane (Tesco Chemical (Hubei) Co., Ltd.); hydroxy silicone oil (Wuhan Hongde Yuexin Pharmaceutical Technology Co., Ltd., 58130-04-4); neopentyl glycol (industrial grade, Wuhan Kangqiong Biopharmaceutical Technology Co., Ltd.); monobutyltin oxide (Haimen Jiusheng Chemical Co., Ltd. (Company), industrial grade); bismuth oxide (Hunan Jintai Bismuth Industry Co., Ltd.); aluminum oxide (Guangzhou Kafen Biotechnology Co., Ltd., model 28395-03-1); aluminum nitride (Hubei Xinhongli Chemical Co., Ltd.).
[0059] The banana pseudostem extract is specifically prepared by the following steps:
[0060] The banana tree is cut to remove the outer sheath and the flower stem, leaving the pseudostem, which is further divided into small pieces and crushed into powder in a grinder. The powder is wrapped in a filter cloth with a pore size of 0.1-0.2 μm, and the filter cloth is squeezed with a hammer to collect juice to obtain a banana pseudostem extract.
[0061] Example 1
[0062] The composite thermal conductive filler is specifically prepared by the following steps:
[0063] A1. Add 4 g of lignin and 0.2 g of nano-nickel powder into 50 mL of deionized water, stir evenly, add 0.2 mL of 5% sodium hydroxide aqueous solution to adjust the pH value to 10, stir at 70 ° C for 40 min, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 60 ° C for 10 min to obtain pretreated nano-metal powder.
[0064] A2. Add 0.5 g of gallium chloride to 30 mL of 0.4 M hydrochloric acid, stir evenly, add 0.3 g of urea, 0.32 g of potassium oxalate and 0.07 g of polyvinyl pyrrolidone, stir for 30 min, add 0.2 g of pretreated nano-metal powder, stir for 30 min, place in a hydrothermal reactor, perform hydrothermal treatment at 180 ° C for 3 h, filter, wash 3 times with deionized water, wash 3 times with ethanol, and dry in an oven at 70 ° C for 30 min to obtain a metal powder loaded with gallium oxide nanosheets.
[0065] A3. Mix 1.2 g of metal powder loaded with gallium oxide nanosheets and 6.5 g of gallium-indium-tin liquid metal, place in an oxygen-free environment, stir and mix at 20°C for 30 minutes to obtain a composite, add 0.5 g of hydroxyboron nitride and 0.7 g of cellulose nanofibers to 50 mL of deionized water, stir and react at 50°C for 1 hour to form a gel, add 1.5 g of the composite to the gel, continue stirring and reacting for 30 minutes, place in a freeze dryer, and freeze-dry at -20°C for 1 hour to obtain a composite thermal conductive filler.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 1 is that the metal powder loaded with gallium oxide nanosheets is replaced by pretreated nano metal powder, and the remaining steps and raw materials are the same as those of Example 1.
[0068] A1. Add 4 g of lignin and 0.2 g of nano-nickel powder into 50 mL of deionized water, stir evenly, add 0.2 mL of 5% sodium hydroxide aqueous solution to adjust the pH value to 10, stir at 70 ° C for 40 min, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 60 ° C for 10 min to obtain pretreated nano-metal powder.
[0069] A2. Mix 1.2 g of pretreated nano-metal powder and 6.5 g of gallium-indium-tin liquid metal, place in an oxygen-free environment, stir and mix at 20°C for 30 minutes to obtain a composite, add 0.5 g of hydroxyboron nitride and 0.7 g of cellulose nanofibers to 50 mL of deionized water, stir and react at 50°C for 1 hour to form a gel, add 1.5 g of the composite to the gel, continue stirring and reacting for 30 minutes, place in a freeze dryer, and freeze-dry at -20°C for 1 hour to obtain a composite thermal conductive filler.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 1 is that hydroxy boron nitride and cellulose nanofibers are not added, and the remaining steps and raw materials are the same as Example 1.
[0072] A1. Add 4 g of lignin and 0.2 g of nano-nickel powder into 50 mL of deionized water, stir evenly, add 0.2 mL of 5% sodium hydroxide aqueous solution to adjust the pH value to 10, stir at 70 ° C for 40 min, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 60 ° C for 10 min to obtain pretreated nano-metal powder.
[0073] A2. Add 0.5g of gallium chloride to 30mL of 0.4M hydrochloric acid, stir evenly, add 0.3g of urea, 0.32g of potassium oxalate and 0.07g of polyvinyl pyrrolidone, stir for 30min, add 0.2g of pretreated nano-metal powder, stir for 30min, place in a hydrothermal reactor, perform hydrothermal treatment at 180°C for 3h, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70°C for 30min to obtain a composite thermal conductive filler.
[0074] Example 2
[0075] The modified silicone resin is specifically prepared by the following steps:
[0076] B1. Add 2.5 g of banana pseudostem extract, 1.8 g of octadecane and 15 mL of tetraethyl silicate to 20 mL of ethanol, and incubate at 50°C for 30 min to obtain an oil phase. Mix 10 mL of anhydrous ethanol, 15 mL of deionized water and 0.5 g of hexadecyltrimethylammonium bromide, and stir at 50°C for 30 min to form an aqueous phase. Mix the aqueous phase and the oil phase, place in a homogenizer, and emulsify at 12,000 rpm for 20 min. Add 0.2 mL of ammonia water to initiate hydrolysis and polycondensation of tetraethyl silicate. After stirring for 2 h, wash three times with deionized water and dry in an oven at 60°C for 10 min to obtain microcapsules.
[0077] B2. Add 2.5 g of polydimethylsiloxane and 1.2 g of microcapsules to 10 mL of deionized water and 50 mL of ethanol, stir evenly, heat to 60°C, stir and react for 30 minutes, filter, wash with deionized water three times, and dry in an oven at 60°C for 10 minutes to obtain pretreated microcapsules.
[0078] B3. Mix 4.2 g of hydroxy silicone oil, 4.1 g of neopentyl glycol and 0.02 g of monobutyl tin oxide, introduce nitrogen, stir and react at 190°C for 2 h, cool to 160°C, add 1.2 g of pretreated microcapsules and 5.9 g of terephthalic acid, heat to 240°C, stir and react until clear and transparent, cool to room temperature, discharge, and obtain a modified silicone resin.
[0079] Comparative Example 3
[0080] The difference between this comparative example and Example 2 is that the microcapsules are replaced with banana pseudostem extract, and the remaining steps are synchronized with Example 2.
[0081] B1. 2.5 g of dimethicone and 1.2 g of banana pseudostem extract were mixed to obtain a mixture.
[0082] B2. Mix 4.2 g of hydroxy silicone oil, 4.1 g of neopentyl glycol and 0.02 g of monobutyl tin oxide, introduce nitrogen, stir and react at 190°C for 2 h, cool to 160°C, add 1.2 g of the mixture and 5.9 g of terephthalic acid, heat to 240°C, stir and react until clear and transparent, cool to room temperature, discharge, and obtain a modified silicone resin.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 2 is that no pretreatment microcapsules are added, and the remaining steps are synchronized with Example 2.
[0085] 4.2 g of hydroxy silicone oil, 4.1 g of neopentyl glycol and 0.02 g of monobutyltin oxide were mixed, nitrogen was introduced, and the mixture was stirred and reacted at 190°C for 2 h. The mixture was cooled to 160°C, 5.9 g of terephthalic acid was added, the mixture was heated to 240°C, the mixture was stirred and reacted until the mixture became clear and transparent, the mixture was cooled to room temperature, and the mixture was discharged to obtain a modified silicone resin.
[0086] Example 3
[0087] A method for preparing a high thermal conductivity material comprises the following steps:
[0088] 30 g of modified silicone resin, 10 g of composite thermal conductive filler, 2 g of bismuth oxide, 1 g of aluminum oxide, and 1.2 g of aluminum nitride were mixed and placed in a mixer. The mixture was stirred and mixed at 170° C. for 15 min. The mixture was cooled to room temperature and ground into powder in a grinder to obtain a high thermal conductive material.
[0089] Example 4
[0090] A method for preparing a high thermal conductivity material comprises the following steps:
[0091] 35 g of modified silicone resin, 13 g of composite thermal conductive filler, 2.5 g of bismuth oxide, 1.5 g of aluminum oxide, and 1.4 g of aluminum nitride were mixed and placed in a mixer. The mixture was stirred and mixed at 170° C. for 15 min. The mixture was cooled to room temperature and ground into powder in a grinder to obtain a high thermal conductive material.
[0092] Example 5
[0093] The forming and coating process of high, medium and low strength aluminum-clad steel wires for optical cable accessories comprises the following steps:
[0094] A method for preparing a high thermal conductivity material comprises the following steps:
[0095] 40 g of modified silicone resin, 15 g of composite thermal conductive filler, 3 g of bismuth oxide, 2 g of aluminum oxide, and 1.5 g of aluminum nitride were mixed and placed in a mixer. The mixture was stirred and mixed at 170° C. for 15 min. The mixture was cooled to room temperature and ground into powder in a grinder to obtain a high thermal conductive material.
[0096] Comparative Example 5
[0097] The difference between this comparative example and Example 4 is that the composite thermally conductive filler is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.
[0098] Comparative Example 6
[0099] The difference between this comparative example and Example 4 is that the composite thermally conductive filler is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.
[0100] Comparative Example 7
[0101] The difference between this comparative example and Example 4 is that the modified silicone resin is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.
[0102] Comparative Example 8
[0103] The difference between this comparative example and Example 4 is that the modified silicone resin is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.
[0104] The performance of the high thermal conductivity materials prepared in Examples 3-5 and Comparative Examples 5-8 is now tested;
[0105] The method for preparing a high thermal conductivity coating for an LED vehicle lamp comprises the following steps:
[0106] After cleaning the dust, oil stains and rust on the LED headlights, a pretreated LED headlight is obtained. The high thermal conductivity material is placed in a cold spray machine and sprayed onto the surface of the pretreated LED headlights to obtain a high thermal conductivity coating for the LED headlights, wherein the pressure of the cold spray machine is 1.45 MPa, the temperature is 90°C, the spraying distance is 25 mm, and the cold spray rate is 150 mm / s.
[0107] The UL-94 standard is used to test the flame retardant performance of the high thermal conductivity coating of LED headlights.
[0108] According to the national standards GB / T1040-2006 and GB / T9341-2000, the tensile strength and bending strength of the high thermal conductivity coating of the LED headlight prepared above were tested; according to the ASTMD5470-2012 "Standard Test Method for Thermal Transfer Characteristics of Thermally Conductive Insulating Materials", the thermal conductivity was measured using a DRL-Ⅲ thermal conductivity tester. The test results are shown in Table 1 below.
[0109] Table 1: Test results
[0110]
[0111] It can be seen from the test results in Table 1 that in Comparative Example 5, the metal powder loaded with gallium oxide nanosheets was not replaced with a composite thermally conductive filler prepared by pre-treating nano-metal powder, and the thermal conductivity thereof was reduced when sprayed onto the LED lamp. This may be because the gallium oxide nanosheets were synthesized on the surface of the pre-treated nano-metal powder to prevent the nano-metal powder from combining easily with oxygen and forming an oxide film on the surface of the nano-metal powder, which resulted in a reduction in thermal conductivity. In Comparative Example 6, hydroxyboron nitride and cellulose nanofibers were not added to prepare the composite thermally conductive filler, and the thermal conductivity and mechanical properties thereof were reduced when sprayed onto the LED lamp. This may be because the network structure of interlaced sheets formed by the cellulose nanofibers and hydroxyboron nitride provided a thermal conductive path for the modified gallium-based liquid metal, so that the core-shell material exerted better thermal conductivity, and the liquid metal was prevented from being heated during the coating process. The microcapsules in comparative example 7 are replaced by modified silicone resin prepared by banana pseudostem extract and sprayed on the LED lamps, and the flame retardant properties thereof are decreased. This may be because the banana extract is mixed with octadecane as the core material and silicon dioxide is used as the wall material to form core-shell microcapsules, which can effectively prevent the leakage and volatilization of the core material of the banana pseudostem extract and improve the service life and performance stability of the banana pseudostem extract. The modified silicone resin prepared by not adding pre-treated microcapsules in comparative example 8 is sprayed on the LED lamps, and the flame retardant properties thereof are decreased. This may be because the microcapsules are grafted on the molecular chains of the silicone resin, giving them excellent flame retardant and insulating properties.
[0112] The data in Table 1 show that the high thermal conductivity materials prepared in Examples 3-5 meet the test performance requirements, while the high thermal conductivity materials prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the high thermal conductivity materials prepared in the present invention have good thermal conductivity, flame retardant properties and mechanical properties, and when sprayed onto LED headlights, they can shield the conductivity of the added metal thermal conductive filler and improve safety performance.
[0113] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0114] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity material, characterized in that: The following steps are involved: S1. mixing a metal powder loaded with gallium oxide nanosheets with a gallium-based liquid metal, and then stirring and reacting with cellulose nanofibers and hydroxyboron nitride to obtain a composite thermal conductive filler; The metal powder loaded with gallium oxide nanosheets is prepared by modifying the surface of lignin with nano metal powder, then mixing with a gallium oxide precursor, and then subjecting the mixture to a hydrothermal treatment. S2. The microcapsules are surface-modified with polysiloxane, and then mixed with hydroxy silicone oil and terephthalic acid to obtain a modified silicone resin; The modified silicone resin is specifically prepared by the following steps: B1. Add polysiloxane and microcapsules to deionized water and ethanol, stir evenly, heat to 60 ° C, stir and react for 30 minutes, filter, wash with deionized water three times, and dry in an oven at 60 ° C for 10 minutes to obtain pretreated microcapsules; B2. The hydroxy silicone oil, neopentyl glycol and monobutyl tin oxide were mixed, nitrogen was introduced, stirred and reacted at 190 ° C for 2h, cooled to 160 ° C, pretreated microcapsules and terephthalic acid were added, heated to 240 ° C, stirred and reacted until clear and transparent, cooled to room temperature, and discharged to obtain a modified silicone resin; The microcapsules are prepared by mixing banana pseudostem extract and octadecane as core material and silicon dioxide as wall material; S3. Mix the modified silicone resin, composite thermal conductive filler, bismuth oxide, aluminum oxide and aluminum nitride, place in a mixer and stir for 10-20 minutes, cool, place in a grinder and grind into powder to obtain a high thermal conductive material.
2. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The nano metal powder is selected from any one of nano nickel powder, nano copper powder and nano aluminum powder; the particle size of the nano metal powder is 2-5 μm.
3. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The gallium oxide precursor is selected from gallium chloride or metallic gallium; the hydrothermal treatment temperature is 160-200° C., and the hydrothermal treatment time is 2-4 hours.
4. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The gallium-based liquid metal is selected from gallium-indium-tin liquid metal, and has a density of 6.4-6.5 g / cm 3 , the surface tension is 718-720m / Nm.
5. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The polysiloxane is selected from any one of polydimethylsiloxane, polymethylhydrogensiloxane, polyphenylmethylsiloxane and dimethyldiphenylpolysiloxane.
6. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The banana pseudostem extract is specifically prepared by the following steps: The banana tree is cut to remove the outer sheath and the flower stem, leaving the pseudostem, which is further divided into small pieces and crushed into powder in a grinder. The powder is wrapped in a filter cloth with a pore size of 0.1-0.2 μm, and the filter cloth is squeezed with a hammer to collect juice to obtain a banana pseudostem extract.
7. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The viscosity of the hydroxy silicone oil is 80-120 mPa·s, and the mass fraction of hydroxyl group is 2.5-3.5%.
8. The method for preparing a high thermal conductivity material according to claim 1, characterized in that: The particle sizes of the bismuth oxide, aluminum oxide and aluminum nitride are 0.1-2 μm; the temperature of the mixer is 150-200° C.
9. An application of a high thermal conductivity material obtained by the preparation method according to any one of claims 1 to 8 in an LED car lamp, wherein the LED car lamp is cleaned of dust, grease and rust to obtain a pre-treated LED car lamp, and the high thermal conductivity material is placed in a cold sprayer and sprayed onto the surface of the pre-treated LED car lamp to obtain a high thermal conductivity coating for the LED car lamp, wherein: The cold spray machine pressure is 1.45MPa, the temperature is 90°C, the spraying distance is 25mm, and the cold spraying rate is 150mm / s.
Citation Information
Patent Citations
Skincare antibacterial microcapsule finishing agent and preparation method and application thereof
CN109554919A
Preparation method of botanical antibacterial flame-retardant cellulose fiber
CN113957558A